How does petty corruption affect tax morale in Sub-Saharan Africa? An empirical analysis - Björn Jahnke (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
Sub-Saharan Africa economies introduced extensive reforms of their tax systems in the last two decades. In most of these countries taxes are now remitted through the self-assessment system that relies on quasi voluntary compliance and audit selection by risk. However, the revenues from direct taxes remained fairly stable and tax/GDP ratios lack behind the industrialized world. Several scholars argue that corruption is one of the major obstacles to increase tax revenues but focus on perceived corruption and remain on the macro-level. This study uses mirco-level data from the Afrobarometer survey wave 5 and thus relates personal corruption experiences to tax morale. The nationally representative survey includes information about corruption experiences in everyday situations when people need to get access to public goods in 31 sub-Saharan African countries. The paper finds that these petty corruption experiences significantly reduce the peoples willingness to pay taxes and hence contribute to the state community. The survey also provides information about trust in tax department in general as well as the perceived number of corrupt tax officials. A mediation analysis estimates that petty corruption experiences not only cause a directly negative effect on tax morale but also have indirectly affect on tax morale via reduced trust in the tax department.
Keywords: D73; H26; K42; F63; 330; corruption; tax morale; institutional and governance quality; economic development